Information Systems Strategic Planning to Improve Elementary School Competitiveness - Dewi, Ratna Mustika; Nastiti, Putri; Negara, Julius Galih; Emanuel, Andi Wahyu Rahardjo (INOVATOR, 2023)
The development of technology is growing very quickly due to the shift in people's lifestyles. This makes it one of the main motivations of investors to be able to create a product as a solution to existing problems in line with the rapid development in the field of technology. The object of this study is elementary schools that have integrity in technological developments. The purpose of this study is to be able to map the Enterprise Architecture (EA) based on the analysis of school needs. The research consists of review focusing on the Internet of Things considering its architecture applied in the Elementary school context in SD Tumbuh 4 Yogyakarta In this case, EA is seen as a logical, comprehensive, and holistic approach to being able to define, design, and implement systems and system components simultaneously. One of the methods used is based on The Open Group Architecture Framework (TOGAF) framework. The stages carried out are Vision Architecture, Business Architecture, Data Architecture, Application Architecture, and Technology Architecture. The analytical tools used in this study are value-chain analysis and mission model canvas. The result of this study is in the form of a proposed application that supports business processes School The application that will be proposed is SIBRO Modification which will support the business process of SD Tumbuh 4 to be more efficient and effective.